2009
DOI: 10.1111/j.1601-183x.2009.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone modulation of α5 nAChR subunits influences anxiety‐related behavior during estrus cycle

Abstract: Smokers often report an anxiolytic effect of cigarettes. In addition, stress-related disorders such as anxiety, posttraumatic stress syndrome and depression are often associated with chronic nicotine use. To study the role of the a5 nicotinic acetylcholine receptor subunit in anxiety-related responses, control and a5 subunit null mice (a5 2/2 ) were subjected to the open field activity (OFA), light-dark box (LDB) and elevated plus maze (EPM) tests. In the OFA and LDB, a5 2/2 behaved like wild-type controls. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 72 publications
1
61
2
1
Order By: Relevance
“…Additionally, there is also evidence showing that other nAChR subtypes may play a role in modulating anxiety as well. For example, Gangitano, Salas, Teng, Perez, and De Biasi (2009) demonstrated that α5 KO animals showed altered hypothalamus–pituitary–adrenal axis function as they were shown to have lower basal corticosterone levels. In addition, while α5 KO animals showed no behavioral changes in the OF and light–dark box paradigms, female KO mice, but not male mice, showed reduced anxiety-like behavior in the EPM.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is also evidence showing that other nAChR subtypes may play a role in modulating anxiety as well. For example, Gangitano, Salas, Teng, Perez, and De Biasi (2009) demonstrated that α5 KO animals showed altered hypothalamus–pituitary–adrenal axis function as they were shown to have lower basal corticosterone levels. In addition, while α5 KO animals showed no behavioral changes in the OF and light–dark box paradigms, female KO mice, but not male mice, showed reduced anxiety-like behavior in the EPM.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…In addition to the β2 and α7 nAChRs, α5 may also be involved in the modulation of depressive-like behavior. For example, using a tail-suspension test and α5 nAChR-null mice, Gangitano et al (2009) found that female but not male α5 KO mice showed reduced depressive-like behavioral phenotype. These studies suggest that inactivation of β2-containing nAChRs along with α7 nAChR activation results in reduction of depression-like behavior in the animal models of depression.…”
Section: Effects Of Nicotine Dependence Withdrawal and Nachr Regmentioning
confidence: 99%
“…Interestingly, progesterone enhances the mRNA expression of the nicotine acetylcholine receptor α5 subunit in mice (Gangitano et al, 2009). To our knowledge, additional data on the regulation of nAChR expression by progesterone are not available in the literature.…”
Section: Mifepristone Reduces Carotid Body and Ventilatory Responses mentioning
confidence: 99%
“…(␣4␤2) 2 ␣5 and (␣4␤2) 2 ␤3 nAChRs are found in the brain, as are (␣6␤2)(␣4␤2)␤3 nAChRs (3, 16 -20). ␣5 and ␤3 subunits have been implicated in nicotine addiction and are likely to be involved in many diseases associated with nAChRs (21)(22)(23)(24)(25)(26)). An ␣5 D398N and some ␤3 polymorphisms are associated with susceptibility to smoking (26,27).…”
mentioning
confidence: 99%